Internalization of Islamic Education Values in Physical Education and Health Subjects at Madrasah Tsanawiyah Binjai City - Khairani, Siti; Budianti, Yusnaili; Sapri (Yayasan Ilomata, 2024)
This study aims to explore the process of internalizing Islamic educational values in physical education and health subjects in the city of Madrasah Tsanawiyah Binjai. Qualitative research methods are used by data collection techniques through participatory observation, in-depth interviews, and document analysis. The results of the study show that physical education and health learning in Madrasah does not only rely on physical aspects, but also integrated Islamic values in each activity. The process of internalizing Islamic educational values occurs through a holistic pedagogical approach, the application of morals and Islam in student interaction, as well as habituation in carrying out physical activities with spiritual awareness. Madrasah environmental factors, the role of teachers, and an integrated curriculum are the main supports in this process. In conclusion, the internalization of Islamic educational values in physical education and health subjects at Madrasah Tsanawiyah Binjai City involves a holistic learning experience, strengthens students' Islamic identity, and provides a foundation for personal, mental and spiritual personal development.